AIR TEMPERATURE EXTREMES IN BELO HORIZONTE: VARIABILITY NATURAL AND INFLUENCE OF URBAN CLIMATE - Jardim, Carlos Henrique; Silva, Marina Rozendo (Revista do Departamento de Geografia, 2016)
Changes in land use and occupation introduced into the environment (agriculture and urbanization, mostly) change the energy balance, interfering with variations of climatic elements. In order to check the temporal dimension of these changes in climate, the maximum and minimum temperature data were analyzed in the cities of Belo Horizonte and Ibirité (Minas Gerais, Brazil), for the period 1961-2014. The analysis procedures included using descriptive statistics and trend analysis and correlation and microclimate analysis techniques and urban climate. The results indicated natural tendency to increase in the maximum and minimum temperature and evidence of human influence on the temporal variation of this climatic element.